An official American Thoracic Society/European Respiratory Society policy statement: Enhancing implementation, use, and delivery of pulmonary rehabilitation - Rochester, C.; Vogiatzis, I.; Holland, A.; Lareau, S.; Marciniuk, D.; Puhan, M.; Spruit, M.; Masefield, S.; Casaburi, R.; Clini, E.; Crouch, R.; Garcia-Aymerich, J.; et al. (2015)
Copyright © 2015 by the American Thoracic Society. Rationale: Pulmonary rehabilitation (PR) has demonstrated physiological, symptom-reducing, psychosocial, and health economic benefits for patients with chronic respiratory diseases, yet it is underutilized worldwide. Insufficient funding, resources, and reimbursement; lack of healthcare professional, payer, and patient awareness and knowledge; and additional patient-related barriers all contribute to the gap betweentheknowledge of the science andbenefits of PR and the actual delivery of PR services to suitable patients. Objectives: The objectives of this document are to enhance implementation, use, and delivery of pulmonary rehabilitation to suitable individuals worldwide. Methods: Members of the American Thoracic Society (ATS) Pulmonary Rehabilitation Assembly and the European Respiratory Society (ERS) Rehabilitation and Chronic Care Group established a Task Force and writing committee to develop a policy statement on PR. The document was modified based on feedback from expert peer reviewers. After cycles of review and revisions, the statement was reviewed and formally approved by the Board of Directors of the ATS and the Science Council and Executive Committee of the ERS. Main Results: This document articulates policy recommendations for advancing healthcare professional, payer, and patient awareness and knowledge of PR, increasing patient access to PR, and ensuring quality of PR programs. It also recommends areas of future research to establish evidence to support the development of an updated funding and reimbursement policy regarding PR. Conclusions: TheATS and ERS commit to undertake actions thatwill improve access to and delivery of PR services for suitable patients. They call on their members and other health professional societies, payers, patients, and patient advocacy groups to join in this commitment.